PLANETARIUM DI BANJARBARU - Sari, Yunita Ambar; Wastuty, Prima Widia (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2022)
Astronomy is one of the oldest sciences of human civilization. In the past, our ancestors navigated the sea using the stars as navigation and the sky as a determinant of the period of cultivation. Astronomy has provided many benefits to our life up to now. Nowadays, astronomical phenomenons are associated with certain beliefs and even the public at large does not yet understand why those occurred. It is very important to socialize Astronomy to support the rapid development of science and technology, so the planetarium can be the answer, as a bridge between humans and science. The architectural problem raised in this design were "What is the design of a planetarium in Banjarbaru that is able to provide spatial experiences with different contexts/stories in each space, has an recreative-educative function, and provides a futuristic visual image with the concept of Space Walkers using the Space Simulation method?" This design was realized by using the Spatial Simulation method as a space for user interaction and the solution to problems using the concept of Space Walkers so that space is not only limited to space but is able to tell stories and provide experiences with different contexts/stories.